The Influence of Fixed Assets and Local Own Revenue on Maintenance Expenditures with Previous Years Budget Balance as Moderation (Study on Aceh Government 2016-2020) - Farisa Rizky Putri; Rita Meutia (Jurnal Akuntansi dan Keuangan, 2023)
ABSTRACTThis research aims to evaluate how the Fixed Assets and locally-generated revenue effect to the original income maintenance expenditure with previous year’s budget balance as moderation in Aceh Province on 2016-2020. This research is a descriptive research. It takes the sample with the census method which makes the entire population as a sample in 115 LKPD.  The population takes a place in all the cities in the Aceh Province. The time span evaluate all the variable effects including the moderating variables to dependent variables and processes by SPSS version 22. The results show that  in Aceh province, Fixed Assets partially have a positive effect on maintenance expenditures, regional original income partially has no effect on maintenance expenditures, the budget of the previous year’s budget has partially had a positive effect on maintenance expenditures, the budget balance is more apparent moderating the effect of fixed assets on maintenance expenditures, the budget is more the previous year artificially moderated the effect of local revenue on maintenance spendin